VD_FINDINFO HC / 2011 / 204 vom 30. März 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, MINIMUM VITAL, REVENU HYPOTHÉTIQUE, CONJOINT, AVANCE DE FRAIS | 163 CC, 277 al. 2 CC, 276 al. 1 CPC (CH), 317 al. 1 CPC (CH)